Urinary Bladder Cancer Risk Factors: A Lebanese Case-Control Study - Kobeissi, Loulou Hassan; Yassine, Ibrahim Adnan; Jabbour, Michel Elias; Moussa, Mohamad Ahmad; Dhaini, Hassan Rida (Asian Pacific journal of cancer prevention : APJCP, 2013)
Bladder cancer is the second most incident malignancy among Lebanese men. The purpose of this study was to investigate potential risk factors associated with this observed high incidence. A case-control study (54 cases and 105 hospital-based controls) was conducted in two major hospitals in Beirut. Cases were randomly selected from patients diagnosed in the period of 2002-2008. Controls were conveniently selected from the same settings. Data were collected using interview questionnaire and blood analysis. Exposure data were collected using a structured face-to-face interview questionnaire. Blood samples were collected to determine N-acetyltransferase1 (NAT1) genotype by PCR-RFLP. Analyses revolved around univariate, bivariate and multivariate logistic regression, along with checks for effect modification. The odds of having bladder cancer among smokers was 1.02 times significantly higher in cases vs. controls. The odds of exposure to occupational diesel or fuel combustion fumes were 4.1 times significantly higher in cases vs controls. The odds of prostate-related morbidity were 5.6 times significantly higher in cases vs controls. Cases and controls showed different clustering patterns of NAT1 alleles. No significant differences between cases and controls were found for consumption of alcohol, coffee, tea, or artificial sweeteners. This is the first case-control study investigating bladder cancer risk factors in the Lebanese context. Results confirmed established risk factors in the literature, particularly smoking and occupational exposure to diesel. The herein observed associations should be used to develop appropriate prevention policies and intervention strategies, in order to control this alarming disease in Lebanon.